Mechanical Properties of Additive Manufactured Complex Matrix Three-Component Carbon Fiber Reinforced Composites; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Chumaevskii A. V.; Kolubaev Е. А. Evgeny Aleksandrovich; Tarasov S. Yu. Sergei Yulievich; Eliseev A. A. Alexander (Materials and Technologies in Powder Metallurgy and Additive Manufacturing, 2016)
Title screen